2023
DOI: 10.1021/jacs.3c08428
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Anti-Markovnikov Hydroamination of Alkenes with Primary Heteroaryl Amines

Eric P. Geunes,
Jonathan M. Meinhardt,
Emily J. Wu
et al.

Abstract: We report a light-driven method for the intermolecular anti-Markovnikov hydroamination of alkenes with primary heteroaryl amines. In this protocol, electron transfer between an amine substrate and an excited-state iridium photocatalyst affords an aminium radical cation (ARC) intermediate that undergoes C−N bond formation with a nucleophilic alkene. Integral to reaction success is the electronic character of the amine, wherein increasingly electron-deficient heteroaryl amines generate increasingly reactive ARCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…Transferring a hydrogen atom from ArS2 onto Int-A- H + needs to overcome significantly higher free-energy barrier than Int-A . This result clarified the blurry detail in the previously proposed mechanism . Furthermore, the preferred ( R )-configuration of the product indicated by computation was consistent with the experimental results, which further verified the rationality of this enantioselective HAT model.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Transferring a hydrogen atom from ArS2 onto Int-A- H + needs to overcome significantly higher free-energy barrier than Int-A . This result clarified the blurry detail in the previously proposed mechanism . Furthermore, the preferred ( R )-configuration of the product indicated by computation was consistent with the experimental results, which further verified the rationality of this enantioselective HAT model.…”
Section: Resultssupporting
confidence: 85%
“…To better understand the enantioselectivity-determining step, a computational investigation was carried out. First, we intended to figure out which species of 3-phenyl-4,4-dimethyl- N -tosyl-3-piperidinyl radical, the charge-neutral ( Int-A ) or N -protonated cationic radical ( Int-A- H + ), is more prone to be the hydrogen-atom acceptor in the HAT process (Scheme a). The barriers for transferring the hydrogen atom from arylthiol onto Int- A and Int-A- H +…”
Section: Resultsmentioning
confidence: 99%
“…Quenching was not observed for any of the aliphatic alkene coupling partners, indicating that this method does not proceed via alkene radical cation intermediates in contrast to seminal work by Nicewicz and co-workers . Through judicious photocatalyst selection, we have subsequently been able to expand this chemistry to realize the catalytic intermolecular anti-Markovnikov hydroamination of unactivated alkenes with primary alkyl amines and more recently, heteroaryl amines (Figure B). , Notably, these reactions selectively form secondary amines with minimal levels of overalkylation products. A detailed mechanistic study of the primary alkyl amine protocol by the Nocera lab resulted in both improved reaction conditions and the development of a scalable flow protocol …”
Section: Intermolecular Anti-markovnikov Hydroamination Of Unactivate...mentioning
confidence: 85%
“…We also observed that a wide variety of functional groups were well-tolerated on the olefin partner, including carbamates (36), lactams (37), acyclic (38) and cyclic ethers (39), as well as esters (40) and unprotected primary alcohols (41). (±)-Linalool underwent regioselective hydroamination favoring reaction at the more electron-rich trisubstituted olefin in the presence of the monosubstituted olefin (42).…”
Section: Scheme 2 Olefin Scopementioning
confidence: 99%